2016
DOI: 10.1007/s11164-016-2590-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of immobilized hexamine on Fe3O4/SiO2 core/shell nanoparticles: a novel catalyst for solvent-free synthesis of bis(indolyl)methanes

Abstract: Hexamethylenetetramine covalently immobilized on silica-coated magnetic nanoparticles is prepared and characterized by XRD, FT-IR, SEM, and VSM. According to SEM pictures, the nanoparticles are mostly spherical in shape, and their size is approximately 46 nm. The catalytic performance of these magnetic nanoparticles for the synthesis of bis(indolyl)methanes was investigated. The catalyst was readily recycled by the use of an external magnetic field and can be reused four times without significant loss of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…16 Although bare Fe 3 O 4 has been utilized for general electrochemical applications, 17,18 Fe 3 O 4 particles have the drawback of aggregation due to nanometer-scale and magnetic effects, which can remarkably decrease their catalytic activity. 19 GAC is commonly used as a carrier for microorganisms and catalysts because it has no biological toxicity, high surface area, and numerous pores that are available for modications or adsorption. 20 It has been reported that Fe 3 O 4 nanoparticles grown on the carbon supports 21,22 have better catalyst dispersibility to enhance the performance of microbial fuel cells (MFC).…”
Section: Introductionmentioning
confidence: 99%
“…16 Although bare Fe 3 O 4 has been utilized for general electrochemical applications, 17,18 Fe 3 O 4 particles have the drawback of aggregation due to nanometer-scale and magnetic effects, which can remarkably decrease their catalytic activity. 19 GAC is commonly used as a carrier for microorganisms and catalysts because it has no biological toxicity, high surface area, and numerous pores that are available for modications or adsorption. 20 It has been reported that Fe 3 O 4 nanoparticles grown on the carbon supports 21,22 have better catalyst dispersibility to enhance the performance of microbial fuel cells (MFC).…”
Section: Introductionmentioning
confidence: 99%
“…This protocol, while employing the identical optimum reaction conditions with Ramshini’s method, managed to reduce the reaction times to 10 minutes with 10 mg of the catalyst and could also facilitate the reaction of ketones. This improved upon the previously known nano-iron oxide methodologies without sacrificing their already satisfying product yields, the recyclability of the nanocatalyst or their environmentally benign aspects, such as the solvent-free conditions without, however, addressing the need for conventional heating that still presented an issue [ 111 ].…”
Section: Reviewmentioning
confidence: 99%
“…The main drawback of the method, however, is the necessity of conventional heating and solvent compared to other methodologies [109,110]. At the same time, Yavari and his research group also studied the use of hexamine, in place of NPS-γ-Fe 2 O 3 , immobilized on Fe 3 O 4 and coated with SiO 2 [111]. This protocol, while employing the identical optimum reaction conditions with Ramshini's method, managed to reduce the reaction times to 10 minutes with 10 mg of the catalyst and could also facilitate the reaction of ketones.…”
Section: Nanocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…41 Ademais, no que se refere à síntese dos BIMs, muitas estratégias sintéticas são descritas quanto ao uso do Fe3O4 nano como suporte para a imobilização de metais de transição, sendo esses materiais utilizados como catalisadores magnéticos nessas reações de alquilação de Friedel-Crafts. [42][43][44][45][46][47] No entanto, o uso direto de Fe3O4 nano como catalisador para esse tipo de reação ainda é raro na literatura. 43 Dessa forma, visando ao desenvolvimento de uma metodologia sintética eficiente, robusta e sustentável para a preparação de compostos BIMs, descrevemos neste artigo o emprego direto do Fe3O4 nano como catalisador da reação de substituição eletrofílica (alquilação de Friedel-Crafts) de indóis e aldeídos.…”
Section: Introductionunclassified